2001
DOI: 10.1007/s00232-001-0069-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Ca 2+ Influx in Leech Retzius Neurons. I. Effect of Extracellular pH

Abstract: We investigated the cytosolic free Ca2+ concentration ([Ca2+]i) of leech Retzius neurons in situ while varying the extracellular and intracellular pH as well as the extracellular ionic strength. Changing these parameters had no significant effect on [Ca2+]i when the membrane potential of the cells was close to its resting value. However, when the cells were depolarized by raising the extracellular K+ concentration or by applying the glutamatergic agonist kainate, extracellular pH and ionic strength markedly af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
2
1
0
Order By: Relevance
“…nels. 15,26 Despite the opposing influence of acidic pH on the magnitude of capsaicin-and high-K ϩ -induced calcium responses, we showed that opioid inhibition of these responses was mutually enhanced by acidic pH. This supports the conclusion that protons modulated opioid receptor-mediated inhibition and did not simply affect stimuli intensity.…”
Section: Discussionsupporting
confidence: 75%
“…nels. 15,26 Despite the opposing influence of acidic pH on the magnitude of capsaicin-and high-K ϩ -induced calcium responses, we showed that opioid inhibition of these responses was mutually enhanced by acidic pH. This supports the conclusion that protons modulated opioid receptor-mediated inhibition and did not simply affect stimuli intensity.…”
Section: Discussionsupporting
confidence: 75%
“…29). Similar dependencies between extracellular pH and Ca 2ϩ entry were found in rabbit-resident alveolar macrophages, neurons, and pancreatic cells (23,30,31). The results presented in this study not only correspond well to these data but also indicate a novel mechanism connecting both extracellular pH and mitochondrial effects on CCE in Jurkat cells.…”
Section: Discussionsupporting
confidence: 75%
“…The ouabain-induced [Ca 2+ ] i increase will be due to the activation of voltage-dependent Ca 2+ channels (see [24]), but it is unclear why [Ca 2+ ] i recovered although the membrane depolarization persisted and why it often increased again after ouabain washout. It is only noted that the activity of the voltage-dependent Ca 2+ channels in Retzius neurons is strongly affected by the extracellular pH and the extracellular Ca 2+ concentration [25,26] and that due to the Ca 2+ affinity of gluconate, the extracellular Ca 2+ concentration of the Cl − -free solution was distinctly lower than that of the physiological solution (see [39]). A contribution of Na + -Ca 2+ exchange to the observed [Ca 2+ ] i changes can be excluded because in Retzius neurons, [Ca 2+ ] i is independent of extracellular Na + ( [23,24]; see Fig.…”
Section: Ouabain-induced Ion Fluxes Across the Plasma Membranementioning
confidence: 99%